The Predictive Role of Osteopontin Level in Patients with Type 2 Diabetes Mellitus without Fatty Liver Disease - AlKenany, Qassim; K. Rasheed, Manal; A. J. AlKazraj , Khalid (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Type 2 diabetes mellitus is a condition in which the body is unable to use insulin effectively. This condition was previously known as non-insulin-dependent or adult-onset diabetes. Osteopontin (OPN) is a phosphorylated glycoprotein initially found in a secreted form in bones. Later, it was discovered that it also exists as an intracellular protein.Objectives: he study aimed to predict Osteopontin levels in type 2 diabetes mellitus patients without fatty liver disease.                                                                     Results: The study found that group A had significantly higher levels of FBS, HbA1c, insulin, HOMA-IR, triglycerides, and VLDL compared to group B (P ≤ 0.05). Additionally, group A had significantly lower levels of HDL than group B. However, there were no significant differences in the levels of cholesterol, LDLc, and ALP between the two groups (P ≥ 0.05). The mean ±SD levels of Osteopontin were 23.66 for group A (DM with NAFLD),. 15.65 for group B (DM without NAFLD), and 5.43 for group C (control group ). This indicates a statistically significant difference (P≤0.05) in the mean ±SD levels of Osteopontin among the studied groups.Conclusion: All parameters are increased in patients with type 2 DM without nonalcoholic fatty liver disease compared to the control group. The recommended threshold for Osteopontin in predicting type 2 diabetes mellitus without non-alcoholic fatty acid liver disease is 9.31 ng/ml.